Elementos da análise funcional para o estudo da equação da corda vibrante - Góis, Aédson Nascimento (2016)
In this work, we are treated some elements of functional analysis such as Banach spaces, inner product spaces and Hilbert spaces, also studied Fourier series and at the end briefly consider the equation of the vibrating string. With this, you realize that you do not need a lot of theory in order to get significant results.